Seminal Changes in Boars After Heat Stress - son, Kjell Lars (Acta Vet Scand, 1984)
The object of the present study was to investigate the influence of elevated ambient temperature on sperm production, sperm morphology and composition of seminal plasma in boars. A total of 8 boars were used, 4 of them were exposed to 35°C, in a climate room, during 100 h and 4 served as controls and were kept at 20°C during 100 h in the climate room. Ejaculate volume and total sperm count per ejaculate remained unaltered. An obvious decrease in sperm motility was seen in all heat exposed boars 15–21 days after the exposure. The most consistent increase in sperm abnormalities were proximal cytoplasmic droplets and abnormal sperm heads. The highest levels were found during the 4th week after exposure. All the sperm characteristics assessed had returned to normal levels at the end of the experimental period, which means 7–8 weeks after the end of exposure. Only minor and inconsistent alterations were found in the seminal plasma components analysed and these changes were observed both in control and experimental boars.